The Process of directing an Interactive Educational Videos for Deaf and Intellectually Disabled Children at SLBN Dharma Wanita Kota Bogor - Astutik, Endang Ayu Puji; Suparman (Lingkar Studi Komunikasi (LISKI), 2025)
Educational videos are familiar to the Indonesian people, especially in the world ofeducation, because educational videos contain certain information or teaching materials that can beused by teachers. The making of educational videos cannot be separated from the role of a directorin the process from start to finish to produce quality audio visual works. Deaf (SLB-B) andIntellectually disabled(SLB-C) students at SLBN Dharma Wanita became the reason for making thisfinal project because they saw that the learning carried out by the school had not used animatedvideos, so the director and team were inspired to make audio-visual works in the form of interactiveeducational videos with the theme "SPESIAL" Sarana, Pembelajaran, Sederhana, Interaktif, Asik danLuar Biasa. The purpose of this final project is to produce an educational video with a curriculumtailored to schools, namely skills and sports, consisting of educational videos to make used goodsuseful, cheerful gymnastics for children with disabilities and Tebak Warna Interaktif (TWI). Dataobtained from primary and secondary data. The directing process of interactive educational videosconsists of three stages: pre-production, production and post-production. The use of laissez fairedirecting technique is applied in making interactive educational videos.